Analisis Kemandirian Keuangan Daerah Kabupaten Sidoarjo Tahun Anggaran 2010 – 2014 - Purnamasari, Dwi; Rodiyah , Isnaini (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
This study aims to determine the level of development of local financial independence Sidoarjo district in order to support the implementation of regional development for the implementation of a decentralized system (Local Government), the contribution of PAD to Sidoarjo district budget in fiscal year 2010-2014 and the commitment of local governments to increase revenue Sidoarjo regency. This type of research is quantitative qualitative (mixed method). The results showed that the ratio of local financial independence Sidoarjoregency status is low or that are in consultative relationship patterns. The ratio of the degree of fiscal decentralization and the index ratio shows the ability of a routine that sufficient fiscal capacity. In harmony ratio shows the results of routine spending a larger share of total development. While the growth rate, the overall experience negative growth. The contribution of PAD to Sidoarjo district budget is low or less. Then the lack of commitment of local governments both the Executive and the Legislature to improve PAD affecting the magnitude of the increase of local financial independence, the lack of loyalty of both the Executive and the Legislature in managing the region's financial sectors ranging from planning to implementation, and the lack of innovation of local governments in exploring the potential Regency Sidoarjo that generate revenue.